Legal Protection for the Work Safety of Langsa City Cleaning Officers - Iskandar, Iskandar; Afnina, Afnina (CV. Rayyan Dwi Bharata, 2024)
This research uses empirical legal research, which assesses the efficiency of law in society. Data collection methods include observation, questionnaires, interviews, and literature review. Based on the results of the study, the relevant agencies have not fully equipped janitors with work safety equipment, janitors often look for reasons not to use work safety equipment, and the relevant agencies have not carried out supervisory duties towards janitors. Obstacles caused by related agencies include related agencies providing work safety equipment that is not in accordance with the work, janitors do not comply with applicable regulations, there are no sanctions against janitors who do not wear work safety equipment, and related agencies do not carry out supervisory functions towards janitors. Efforts that need to be made by related agencies include providing complete work safety equipment, reminding foremen to remind their subordinates to wear work safety equipment, supervising janitors, conducting socialization about the dangers of not wearing work safety equipment, and imposing sanctions on janitors who do not wear work safety equipment.